2021
DOI: 10.1016/j.resuscitation.2021.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Survival probability in avalanche victims with long burial (≥60 min): A retrospective study

Abstract: Background: The survival of completely buried victims in an avalanche mainly depends on burial duration. Knowledge is limited about survival probability after 60 min of complete burial. Aim:We aimed to study the survival probability and prehospital characteristics of avalanche victims with long burial durations. Methods:We retrospectively included all completely buried avalanche victims with a burial duration of !60 min between 1997 and 2018 in Switzerland.Data were extracted from the registry of the Swiss Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 31 publications
0
10
1
Order By: Relevance
“…A retrospective study analyzed the survival probability in avalanche victims with long burial (≥60 min) and identified several correlating parameters 4 : the median burial depth of survivors (70 cm) was significantly more superficial than for those who died (100 cm). 4 Our avalanche victim survived, despite being buried 230 cm below the snow surface, therefore contradicting this study. The same study reported that the estimated survival probability dropped from 23% after 60 min of burial duration to less than 6% after 1400 min, approximately 24 h. 4 The odds ratio of the decrease in survival was 0.93 per hour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study analyzed the survival probability in avalanche victims with long burial (≥60 min) and identified several correlating parameters 4 : the median burial depth of survivors (70 cm) was significantly more superficial than for those who died (100 cm). 4 Our avalanche victim survived, despite being buried 230 cm below the snow surface, therefore contradicting this study. The same study reported that the estimated survival probability dropped from 23% after 60 min of burial duration to less than 6% after 1400 min, approximately 24 h. 4 The odds ratio of the decrease in survival was 0.93 per hour.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Reasons for a good outcome after long avalanche burial in an open area include the presence of a large or open-air pocket, no obvious major injuries, victims well insulated to avoid fast and critical cooling within hours, and no hypothermic or asphyctic cardiac arrest. A retrospective study analyzed the survival probability in avalanche victims with long burial (≥60 min) and identified several correlating parameters 4 : the median burial depth of survivors (70 cm) was significantly more superficial than for those who died (100 cm). 4 Our avalanche victim survived, despite being buried 230 cm below the snow surface, therefore contradicting this study.…”
Section: Long Burial Timementioning
confidence: 99%
“…Delayed extrication of avalanche victims is associated with reduced survival and worsened clinical outcome. 4,17,18 Rescue algorithms for avalanche accidents should consider the potential of prolonged search and rescue missions from EMI caused by electric devices. 5,19 Furthermore, EMI caused by HE was more pronounced in rescuer ATs.…”
Section: Discussionmentioning
confidence: 99%
“…The widespread belief that victims with long burial times have less chance of survival is incorrect. Victims with long burials who are not asphyxiated may be protected from brain injury by hypothermia and can have good neurological outcomes [6,30]. Resuscitation efforts should be withheld, according to BLS guidelines, if the victim is not hypothermic (QI 14) or if the victim has had a long burial with obstructed airway and asystole (QI 15).…”
Section: Patient Managementmentioning
confidence: 99%